Match-Play Demands of Elite Youth Gaelic Football Using Global Positioning System Tracking. Issue 4 (April 2015) - Reilly, Brian; Akubat, Ibrahim; Lyons, Mark; Collins, D. Kieran
Abstract : Abstract: Reilly, B, Akubat, I, Lyons, M, and Collins, DK. Match-play demands of elite youth Gaelic football using global positioning system tracking. J Strength Cond Res 29(4): 989–996, 2015—Global positioning systems (GPS) technology has made athlete-tracking a convenient and accepted technique to specify movement patterns and physical demands in sport. The purpose of this study was to examine positional demands of elite youth Gaelic football match-play using portable GPS technology to examine movement patterns and heart rates across match periods. Fifty-six elite youth male Gaelic footballers (age, 15 ± 0.66 years) fitted with portable 4-Hz GPS units were observed during 6 competitive matches (60 minutes). Data provided from the GPS unit included total distance, high-intensity (≥17·km·h −1 ) distance, sprint (≥22 km·h −1 ) distance, and total number of sprints. Heart rate was monitored continuously throughout the games. Players covered a mean distance of 5732 ± 1047 m, and the mean intensity of match-play was 85% of the peak heart rate. There was a significant ( p = 0.028) drop in the total distance covered in the second half (2783 ± 599 m) compared with the first half (2948 ± 580 m). In particular, there is a noticeable drop in the distance covered in the third quarter of the game (after half-time), which has implications for re-warming up at the end of the half-time interval. There was a highly significant ( p < .001) difference in the distance traveled across the 5 positional groups with midfielders covering the greatest total distance (6740 ± 384 m). The significant differences found with respect to positional groups support the implementation of individual, position-specific strength and conditioning programs.